Human milk vs. cow-milk based infant formula proteins: structure, digestion and physiological impacts - Chauvet, Lucile; Charton, Elise; Lemaire, Marion; Le Huërou-Luron, Isabelle; Deglaire, Amélie (Frontiers in Nutrition, 2025)
This review examines the differences in protein composition, digestion, and physiological effects on infants between human milk (HM) and infant formula (IF). The World Health Organization recommends exclusive breastfeeding for the first 6 months of life due to the numerous health benefits associated with it. However, when this is not possible, IF is used as an alternative. Differences between HM and IF remain, particularly in terms of protein composition and structure. Further optimization of IF is needed to better mimic HM and provide similar health benefits. Further improving IF formulation requires implementing a promising strategy, which in turn requires a thorough understanding of the mechanisms of protein digestion and amino acid (AA) absorption, as well as the metabolic and physiological effects of protein composition and structure. These are often altered by heat treatment and processing in IF. The main differences in the protein composition and structure of HM and IF are presented, including a synthesis of knowledge on the non-protein nitrogen (NPN) fraction. This fraction is too often neglected in milks, despite accounting for one fifth of the total nitrogen in HM. The influence of the protein composition and structure of HM and IF on the digestion of dietary protein and dietary AA absorption is compared, highlighting the need for data on the postprandial AA profile in infants from well-designed clinical trials. Finally, this review examines the differences in protein composition and digestion between HM and IF that lead to distinct metabolic, physiological and microbial outcomes. Future research should focus on understanding the role of partially digested proteins and the NPN fraction in shaping the infant gut microbiota and overall health.